(untitled) (Annual of the Faculty of Philosophy in Skopje, 2012)
Even after so many years the scientific public is still leading debates on the role and value of play and its influence on effective teaching and learning. The reasons for and against play in an educational context produce arguments which have placed it on a high level in the program for educational policies, research and practice. Play has still been given serious treatment, and this has been confirmed by contemporary research which provide new theoretical frameworks and practice guides. Scientists and practitioners alike view the issue ofplay with particular interest, especially for its ideal mixture of theory and practice, as well as the fact that it generates quality in the process of learning and teaching. The didactic-methodic ordering of the play activity refers to its thought- out planning and creating a structure that will determine the individual elements in its realization. Practice offers different interpretations of the term structure. For example, on the one hand the structure might imply a narrow methodic framework which focuses its attention on different teaching final results. On the other hand though, the structure might imply an open methodic framework which gives a sense of security that the play activities include the process that supports learning and has the potential to offer possibilities for final results. Both interpretations depend on the pedagogical context in which the given structure is being realized. Teachers have to recognize the different meanings so as to decide which approach and didactic-methodic components they will apply for the result of creating an interdependent relationship between play, learning and teaching in the first educational cycle.